Some Cicadelline lectotypes of Breddin species (Homoptera: Cicadellidae). - Young, David Allan jun. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
There is given a list of Cicadellidae-lectotypes of species described by G. Breddin in preparation for a revision of the genera of Cicadellinae now in progress by the author. Nomenclatural Actshebetula Breddin, 1903 (Conogonia), Lectotypeplacidula Breddin, 1903 (Conogonia), Lectotypeaureatula Breddin, 1901 (Sphaeropogonia), Lectotypefacula Breddin, 1901 (Sphaeropogonia), Lectotypequincuncula Breddin, 1901 (Sphinctogonia), Lectotypereginula Breddin, 1901 (Sphinctogonia), Lectotypeservula Breddin, 1901 (Sphinctogonia), Lectotypeatramentatula Breddin, 1901 (Tettigonia), Lectotypecarfbuncula Breddin, 1901 (Tettigonia), Lectotypecruciatula Breddin, 1902 (Tettigonia), Lectotypecruentula Breddin, 1901 (Tettigonia), Lectotypeferrugatula Breddin, 1901 (Tettigonia), Lectotypegryllula Breddin, 1901 (Tettigonia), Lectotypelacertula Breddin, 1901 (Tettigonia), Lectotypelarvatula Breddin, 1902 (Tettigonia), Lectotypemellatula Breddin, 1901 (Tettigonia), Lectotypemelliguttula Breddin, 1901 (Tettigonia), Lectotypemultilunatula Breddin, 1901 (Tettigonia), Lectotypeserenula Breddin, 1901 (Tettigonia), Lectotypeserratula Breddin, 1902 (Tettigonia), Lectotypestillatula Breddin, 1902 (Tettigonia), Lectotypevespertinula Breddin, 1903 (Tettigonia), Lectotypeardentula Breddin, 1901 (Trichogonia), Lectotypeisabellula Bredddin, 1901 (Trichogonia), Lectotypehaenschi Breddin, 1902 (Zyzzogeton), Lectotype